Neighbourhood safety and academic performance: the role of student gender and family socioeconomic status - N. Ali; U. Daraz; . Ibrahim; M. Hussain; Y. Khan; S. Ali (Образование и наука)
Introduction. Neighbourhood safety is directly linked to the level of disadvantage in the area of residence. Aim. The present research aimed to examine the impact of neighbourhood safety on the academic performance of secondary school students, taking into account gender and socioeconomic background. Methodology and research methods. The current study used a quantitative cross-sectional study design. Data were collected from 448 secondary school students on a voluntary basis. Chi-square and Kendall’s Tau-c (Tc) tests were used to analyse the data and determine the relationship and strength of direction between variables. Results. The findings indicated a significant and positive association between children’s academic performance and neighbourhood crime safety (P < 0.05, Tc = 0.202), as well as feeling safe, walking in the neighbourhood during the day or night (P < 0.05, Tc = 0.127). However, bullying and harassment in the neighbourhood were found to be significantly and negatively associated with academic performance (P > 0.05, Tc = -0.053). When introducing family socioeconomic status as a control variable, the results indicated variation in academic performance in relation to neighbourhood safety. When controlling for student gender, neighbourhood safety had no different effects on academic performance. The findings showed that, in relation to neighbourhood safety, children from families with higher socioeconomic status academically outperform children from lower socioeconomic status families. Scientific novelty. The study not only focused on the connection between neighbourhood safety and academic performance but was also unique in the sense that it also dealt with differences in academic performance based on gender and family socioeconomic level. Practical significance. The study produces a number of interesting conclusions and makes valuable recommendations for significant stakeholders. The primary study recommendations aim is to create a secure, supportive, and protective neighbourhood environment by enforcing the law and encouraging community involvement in order to reduce the threat of crime, violence, and harassment.